The influence of the literacy environment on children’s writing development in Chinese - Su, Mengmeng; Fan, Yi; Wu, Jifeng; Qiao, Bingyan; Zhou, Wei (Frontiers in Psychology, 2022)
The present study investigated the influence of literacy learning experience at home and outside home on the performance of writing narratives for primary school students. Two hundred and fifty Chinese children participated in this study. There were 146 third graders (71 boys, 75 girls) and 104 fifth graders (53 boys, 51 girls). Results showed that children’s writing abilities increased at the word level and sentence level from third grade to fifth grade. Literacy experience at home (the character learning at home) predicted the writing performance of third graders, while literacy experience outside home (the visiting frequency of various places outside home) predicted the writing performance of fifth graders. After controlling the effect of reading efficiency on the writing skills, the prediction of literacy learning experience at home and outside home on the writing performance remained. The results suggest the importance of literacy experience at home and outside home on the writing development of primary school students.